Generating textual captions for ultrasound visuals in an automated fashion - Alsharid, M (2021)
Generating captions for ultrasound images and videos is an area that is yet to be fully studied and explored. The aim of the work in this thesis is to learn joint image-text representations to describe ultrasound images with rich vocabulary consisting of nouns, verbs, and adjectives. Preparing medical image captioning benchmarks is challenging for two reasons: (a) describing medical images with specific terminology requires expert knowledge of medical professionals; and (b) the sensitive nature of medical images prevents wide-scale annotation, for instance, using crowd-sourcing services (e.g. Amazon Mechanical Turk) and similar methods. Therefore, automatic image captioning has not been widely studied on ultrasound images before, the challenge being enhanced by the lack of readily available large datasets of ultrasound images with captions.